رقمنة العروض العربي: نماذج من تطبيقات الحوسبة - محمد، سعدية مصطفى (جامعة القاهرة - كلية دار العلوم, 2021)
Al-Khalil bin Ahmed Al-Farahidi (d. 175 AH) established the science of prosody with a mathematical intuition; This is an interdisciplinary study that combines Arabic presentations and mathematics, and its fruit has grown through Applications, which facilitated the manipulation of hair automation for the vowel and (1) for the weights by the two numbers (.) consonant, and these two numbers on which the computer was We also used decimal numbers for ease, created, The numbers are replaced by cross-cutting of the activations, so The digital shows depended on the verbal description is reduced. audio clips, as in the two numbers: 2 3 The content of the digital shows added new meanings to the seas of poetry, the identity of the sea is fixed, As for his interruptions, they are numerous; This allows the sea to enter a new circle, which Hebron did not specify. Among those who contributed to the digitization of the offers: 1- Model D. Muhammad al-Katib, then a team of computer scientists- in his own way- implemented a program Entitled: Application of Computerizing the Scales of Arabic Poetry 2009. 2- The Jalal Al-Hanafi model, then the researcher Jenan Al-Eidani applied a computer program to it. 3- Model Dr. Ahmed Mostajir. and finally I dealt with Al-Farahidi program; For its ease and availability For users, it showed the relationship between language and geometry. Authentic Arabic poetry can be weighed in a modem scientific way, using the most recent The scientific methods used in our time, which is the computer, is a revival of our Arab heritage.
أسس الخليل بن أحمد الفراهيدي (ت 175ه) علم العروض بحدس رياضي، لذلك أنشأ موازين الشعر العربي على خمس دوائر. هذه دراسة بينية تجمع بين العروض العربي والرياضيات، وقد أينعت ثمرتها بأتمتة التطبيقات، التي يسرت معالجة أوزان الشعر عن طريق الرقمين الثنائيين (0) للحرف المتحرك و(1) للحرف الساكن، وهذان الرقمان نشأ عليهما الحاسوب، وأيضا استعملنا الأرقام العشرية لسهولتها. تستبدل الأرقام بالتقطيع العروضي للتفعيلات، لهذا يتم تقليص الوصف اللفظي. اعتمد العروض الرقمي على المقاطع الصوتية، كما في الرقمين: 2 3 أضاف مضمون العروض الرقمي دلالات جديدة لبحور الشعر، فهوية البحر ثابتة، أما مقاطعة فإنها تتعدد، مما يسمح للبحر بالدخول في دائرة جديدة، لم يحددها الخليل. ومن الذين أسهموا في رقمنة العروض: 1-نموذج د. محمد الكاتب، ثم طبق فريق من الحاسوبيين- على طريقته- برنامجا بعنوان: تطبيق حوسبة موازين الشعر العربي، 2009م. 2-نموذج جلال الحنفي، ثم طبقت الباحثة جنان العيداني برنامجا حاسوبيا عليه. 3-نموذج د. أحمد مستجير، وأخيرا تناولت برنامج الفراهيدي، لسهولته وتوفره للمستخدمين، حيث أظهر العلاقة بين اللغة والهندسة. -يمكن أن يوزن الشعر العربي الأصيل بطريقة علمية حديثة، تستعمل فيها أحدث الأساليب العلمية المتبعة في عصرنا هذا، وهو الحاسوب، وهذا يعد إحياء لتراثنا العربي.
Keywords: الشعر العربي -- الأوزان الشعرية -- علم العروض -- العروض الرقمي -- رقمنة علم العروض -- حوسبة علم العروض